(untitled) (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
In the contemporary society, children need to become competent internet users. Previous studies suggested that in order to achieve this goal, it helps if children understand basics of how internet works. However, these studies also indicated that children’s knowledge about internet’s functioning is patchy. Furthermore, children possess many misconceptions and existing research does not examine how to boost their understanding of the internet’s functioning. Here, we present a mixed-method study, in which children (Grade 4, 6, 8; N = 50 + 50 + 38): a) were interviewed about how the internet works; b) half of them (random assignment) was explained this topic during a 50-min-long 1:1 tutoring session (with activating tasks); c) were interviewed again four months later. The interviews and the teaching session examined/promoted understanding of the following concepts: servers, wifi routers, network routers, wireless vs. wire connection, storage of data on the internet, digital traces, and cookies; among others. The interviews are now being analysed through thematic and frequency analyses. Preliminary findings corroborate previous findings about misconceptions and are consistent with ‘knowledge in pieces’ theories of knowledge representations. Typical reasoning among children about the internet structure includes satellites and central computers/towers. Only expert children know about distributed, server-like storage. Children understand the internet primarily through their personal experiences, only most knowledgeable children view it as a global network with a complex internal, but only vaguely understood, structure. The teaching session promoted understanding in short term, but much less so in a long term. Four months later, only few children retained knowledge about network routers, some about servers. Children tended to return to their prior misconceptions and their post-understanding remained patchy. Some held both prior misconceptions and contradictory new ideas. Altogether, our results suggest that teaching K-8 children about the internet functioning will be challenging and specific approaches, such as those capitalizing on activating children’s prior knowledge, will be required.